Therapy with un-engineered naïve rat umbilical cord matrix stem cells markedly inhibits growth of murine lung adenocarcinoma - Maurya, Dharmendra K (BioMed Central, 2010)
BACKGROUND: Lung cancer remains the leading cause of cancer-related mortality despite continuous efforts to find effective treatments. Data from the American Cancer Society indicate that while the overall incidence of lung cancer is declining, it continues to rise in women. Stem cell-based therapy has been an emerging strategy to treat various diseases. The purpose of this paper is to determine the efficacy of an intrinsic anti-cancer effect of rat umbilical cord matrix stem cells (UCMSCs) on lung cancer. METHODS: A mouse syngeneic lung carcinoma model was used to test the basic ability of UCMSCs to control the growth of lung cancer. Lung tumors were experimentally induced by tail vein administration of Lewis lung carcinoma (LLC) cells derived from the lung of C57BL/6 mouse. Rat UCMSCs were then administered intratracheally five days later or intravenously on days 5 and 7. The tumor burdens were determined by measuring lung weight three weeks after the treatment. RESULTS: Co-culture of rat UCMSCs with LLC significantly attenuated the proliferation of LLC cells as monitored by MTT (3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide), a tetrazole cell proliferation assay, thymidine uptake, and direct cell counts. In vitro colony assays with rat UCMSCs as feeder layers markedly reduced LLC colony size and number. Co-culture of rat UCMSCs with LLCs causes G0/G1 arrest of cancer cells. This is evident in the decrease of cyclin A and CDK2 expression. The in vivo studies showed that rat UCMSC treatment significantly decreased tumor weight and the total tumor mass. Histological study revealed that intratracheally or systemically administered rat UCMSCs homed to tumor areas and survived for at least 3 weeks without any evidence of differentiation or adverse effects. CONCLUSIONS: These results indicate that rat UCMSCs alone remarkably attenuate the growth of lung carcinoma cells in vitro and in a mouse syngeneic lung carcinoma graft model and could be used for targeted cytotherapy for lung cancer.